Factors that influence the behavior of voters in Kota Bharu, Kelantan / Zia Ul-Ariff Nazman and Muhamad Syakir Mohd Noor - Nazman, Zia Ul-Ariff; Mohd Noor, Muhamad Syakir (2022)
The purpose of the study was to identify the factors that influence the voting behavior of voters in Kota Bharu, and which factors that influenced the voting behavior most. The study was carried between March and July 2022. The study used simple random sampling techniques in collecting the survey data. The result of the study revealed that the most significant factors that influence the voting behavior in Kota Bharu is candidate image compared to other factors which are current events and media.